Effect of linear side-chain length on the photovoltaic performance of benzodithiophene-alt-dicarboxylic ester terthiophene polymers. (29th July 2019) - Ma, Kangqiao; Zhang, Tao; Wan, Pan; Xu, Bowei; Zhou, Pengxin; An, Cunbin
Abstract : Two conjugated polymers with different side chains were synthesized to study their photovoltaic performances. Abstract : Conjugated polymers (P3TE-C8 andP3TE-C12 ) with two different side chains based on thienyl-substituted benzodithiophene and dicarboxylic ester terthiophene were synthesized and applied in non-fullerene polymer solar cells (PSCs). Detailed studies revealed that the length of side chains in conjugated polymers showed a weak influence on their optical bandgaps and electrochemical properties, but a strong influence on their aggregation behaviors in solution, films, bulk heterojunction morphologies and photovoltaic performances. Among PSC devices, theP3TE-C8 :ITIC-based device showed a PCE of 5.49%, a V OC of 0.814 V, J SC of 12.86 mA cm −2 and FF of 52.48%, while theP3TE-C12 :ITIC-based device exhibited a higher PCE of 7.64%, with simultaneously improved photovoltaic parameters of V OC of 0.906 V, J SC of 14.20 mA cm −2 and FF of 59.36%. This work demonstrates that the reduction aggregation in conjugated polymers via changing the length of side chains is an effective method to improve PSC performances.